Reserves for stimulating household final consumption in the Northwestern District of Russia - E.G. Leonidova (Управленец)
Expanding production and product sales in the domestic market is the key task facing Russian manufacturers amid Western economic sanctions. At the same time, due to wage stagnation, a number of the RF regions are characterised by low level consumption. The purpose of the article is to identify reserves for promoting household final consumption at the regional level using the case study of the RF Northwestern Federal District (NWFD). Methodologically, the study rests on social reproduc tion theory and the concept of national accounts. The research methods include comparative analysis and synthesis, as well as economic, statistical and macrostructural analysis. Empirical data were retrieved from the Federal State Statistics Service (Rosstat), the Unified Interdepartmental Statistical Information System (EMISS) and regional authorities’ official websites. An undercon sumption trend was revealed in a number of the NWFD regions, adversely affecting the socio-economic situation in them. The northwestern regions of Russia are proved to have a potential to hasten transformation processes aimed at improving the quality of economic growth by boosting household consumption. This is possible through an increase in household income and redis tribution of income in the economy, implementation of structural policies focused on enhanced labour productivity, developing promising economic specializations, and extending value chains. The paper discusses prospective avenues for encouraging pro duction of locally manufactured goods in the northwestern regions (the oblasts of Vologda, Leningrad and Murmansk, and the Republic of Karelia).